3D dynamical structuring of a high latitude erupting prominence: I- Analysis of the cool plasma flows before the eruption. Issue Volume 8:Issue S300(2013) (6th January 2014) - Koutchmy, Serge; Filippov, Boris; Tavabi, Ehsan; Bazin, Cyril; Weiller, Sylvain
Abstract: Both the origin of the quiescent prominences and their eruption related to CMEs are still a matter of extended studies. The small scale dynamic aspects like vortex structures and counter- flows are now seriously taken into account having in mind that the flows are a good proxy of the line of force of the omnipresent but rather unknown in detail force free or not magnetic field. Large scale vortex has been detected in a high latitude prominence observed on November 13- 14, 2011 before its eruption.